PELAKSANAAN SISTEM ADMINISTRASI AKADEMIK DI UNIVERSITAS ISLAM JEMBER - jurnalmap map; Ach. Ilyasi; Hadi Susanto; Sri Juni Woro Astuti (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
This study discusses to discuss the academic administration system, obstacles that occur in the academic administration system and efforts to overcome the academic administration system constraints at the Islamic University of Jember. This research is a descriptive qualitative research. Data collection methods used in this study are: interviews, document studies and observations. The results of research on the implementation of the academic administration system at the Jember Islamic University show: (1) planning has not been formally carried out at the time of the implementation, (2) coordination has not been carried out programmatically among others, working less harmoniously, (3) monitoring and not carried out programmatically. The main obstacle in the academic administration system at the Islamic University of Jember is the lack of proper coordination and evaluation in every activity.Keywords: academic administration system, Islamic University of Jember